2020
DOI: 10.1051/0004-6361/201936434
|View full text |Cite
|
Sign up to set email alerts
|

AGN feedback in a galaxy merger: multi-phase, galaxy-scale outflows with a fast molecular gas blob ∼6 kpc away from IRAS F08572+3915

Abstract: To understand the role that AGN feedback plays in galaxy evolution we need in-depth studies of the multi-phase structure and energetics of galaxy-wide outflows. In this work we present new, deep (∼ 50 hr) NOEMA CO(1-0) line observations of the molecular gas in the powerful outflow driven by the AGN in the ultra-luminous infrared galaxy IRAS F08572+3915. We spatially resolve the outflow, finding that its most likely configuration is a wide-angle bicone aligned with the kinematic major axis of the rotation disk.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 137 publications
2
28
0
Order By: Relevance
“…The corresponding momentum ratio is of the order of ζ =ṗ/(L/c) ∼ 20 and the energy ratio is ǫ k =Ė k /L ∼ 0.04. The high values of the outflow energetics measured in this source have been exclusively interpreted in the framework of the wind energydriving scenario (Herrera-Camus et al 2020).…”
Section: Individual Comparisonmentioning
confidence: 81%
See 3 more Smart Citations
“…The corresponding momentum ratio is of the order of ζ =ṗ/(L/c) ∼ 20 and the energy ratio is ǫ k =Ė k /L ∼ 0.04. The high values of the outflow energetics measured in this source have been exclusively interpreted in the framework of the wind energydriving scenario (Herrera-Camus et al 2020).…”
Section: Individual Comparisonmentioning
confidence: 81%
“…A molecular outflow was previously detected in CO observations, with an average velocity of ∼800 km s −1 (Cicone et al 2014), and the corresponding outflow energetics are reported in Fluetsch et al (2019). New high angular resolution CO observations spatially resolve the molecular outflow, which has an outflowing mass of M ∼ 3 × 10 8 M ⊙ and reaches a velocity of v ∼ 1200 km s −1 around ∼1 kpc (Herrera-Camus et al 2020). The associated mass outflowrateisṀ ∼ 350 M ⊙ yr −1 , while the outflow momentum rate and kinetic power areṗ ∼ 3 × 10 36 dyn andĖ k ∼ 2 × 10 44 erg s −1 , respectively.…”
Section: Individual Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in the Seyfert galaxy IC 5063, a remarkable kinematic similarity between the ionized, neutral atomic, and the molecular phase was found (Morganti et al 2015;Oosterloo et al 2017), suggesting a link between the different phases. Similarly, HE 1353−1917 (Husemann et al 2019) and IRAS F08572+3915 (Herrera-Camus et al 2020) also display co-spatiallity between the molecular and the ionized outflow phase. In other galaxies, such as Mrk 231 (Feruglio et al 2015), the interplay between gas phases appears to be much more complex and there might have been several feedback episodes.…”
mentioning
confidence: 93%